FORTIFIKASI SARI DAUN KELOR UNTUK MENINGKATKAN MUTU JELLY DRINK DALUMAN : Fortification of Moringa Leaf Juice to Improve Quality of Daluman Jelly Drink - Ana Juliana; Siska Cicilia; Zainuri Zainuri (Pro Food, 2023)
Jelly drink is a drink made of fruit juice. In general, jelly drink is only a source of vitamins, minerals, fiber and sodium, while the content of other nutrients such as protein is still relatively low. The aim of this study was to discover the effect of fortification of moringa leaf juice on the quality of daluman jelly drink. This study used Completely Randomized Design (CRD) with a single factor, namely the fortification of moringa leaf juice which consisted of 6 treatments including 0%, 10%, 20%, 30%, 40% and 50%. Each treatment was repeated 3 times to obtain 18 experimental units. The jelly drink parameters tested were chemical quality (protein and vitamin C content), physical quality (color and texture) and organoleptic quality (color, aroma, texture and taste). Data were analyzed by the Anova using Co-stat Software at the 5% level and further tested using the Honest Significant Difference (HSD) test. The treatments significantly affected the protein and vitamin C content, lightness, texture, aroma and taste of daluman jelly drink. The treatment of 20% moringa leaf juice was recommended as the best treatment to improve quality of daluman jelly drink with a protein content of 7.44%; vitamin C content 87.82 mg/100g; lightness 19.85; oHue value 188,42; texture 0.30 (N), and the organoleptic properties were rather preferred by the panelists